International Law on Marine Pollution from Ballast Water - Efanie, Nadia (Indonesian Journal of International Law, 2011)
Introduction of non-indigenous (alien) species in ballast water from ships are one of the greatest threats to marine ecosystem worldwide. New approaches to prevent and reduce the release of Alien Invasive Species (AIS) from ballast water are under consideration nationally and internationally. Problem that arise from this kind of pollution not only has impact on environmental, but also in some aspects like health, shipping and biodiversity. Based on this matter, IMO as the responsible organization about marine matter, adopted a new convention namely as The International Convention for the Control and Management of Ships’ Ballast Water and Sediments on February 2004. The legal framework on ballast water comprises a complex of interconnected provisions.